2x-3=2x

Simple and best practice solution for 2x-3=2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-3=2x equation:


Simplifying
2x + -3 = 2x

Reorder the terms:
-3 + 2x = 2x

Add '-2x' to each side of the equation.
-3 + 2x + -2x = 2x + -2x

Combine like terms: 2x + -2x = 0
-3 + 0 = 2x + -2x
-3 = 2x + -2x

Combine like terms: 2x + -2x = 0
-3 = 0

Solving
-3 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 5+3p^2=17 | | 1-8z+6-6z=0 | | 2x-7-(x-5)=0 | | -24=6(5-3x) | | n^2-4n-18=3 | | 15c^2=96 | | 13-36x^2=-12 | | 12=5b-2a | | 9+4(x-5)=2x-3 | | 2(3z-10)=40 | | x+4y=25 | | -1.5=-75 | | y=-4x^2+6x-8 | | -7y+13+9y+1=4 | | 12=5a-2b | | 6x+6=3(x-2) | | 7x+(-2)=-44 | | 2c(c^5+4c^3)= | | 3q(4-q+3q^3)= | | -t(5t^2+t)= | | (x-16)-(2x-13)=1 | | 5y-12x=-3 | | 8x-2=y | | (3c-4c^2+c^3)-(5c^2+8c^3-6c)= | | (-4m^2+m-10)+(3m+12-7m^2)= | | 5+3x=3+5x | | 8w-5=35-12w | | x-2x=200 | | (9a^2-4-5a)-(12a-6a^2+3)= | | x-2x=300 | | (3+5i)-(4-6i)= | | -17=6x-(1+2x) |

Equations solver categories